Insider trading surrounding securities class action litigation and settlement announcements. Issue 1 (9th January 2017) - Davis, Frederick; Taghipour, Behzad; Walker, Thomas J.
Abstract : Purpose: The purpose of this paper is to investigate the trading patterns of corporate insiders, both managing and non-managing, around the announcement dates of securities class action lawsuits and related legal settlements. Design/methodology/approach: The authors use market model event study methodology to examine the impact of class action litigation and settlement announcements on the stock prices of sued firms. The authors then determine the extent of abnormal insider trading surrounding such announcements by comparing insider trading activity (volume and transaction counts) to prior insider trading in the same firm, and to a matched sample of firms not experiencing such litigation announcements. A multivariate framework is utilized to provide further insight into the determinants of such abnormal insider trading. Findings: The authors establish that class action litigation and settlement announcements have a significant impact on the stock prices of sued firms, and that foreknowledge of these events appears to be used by insiders to earn abnormal profits. Moreover, results indicate that managing insiders exhibit higher opportunistic abnormal trading activity than non-managing insiders. Multivariate analysis shows that size, prior firm returns, and the implementation of the Sarbanes-Oxley Act are important determinants of such insider trading. Originality/value: This appears to be the first paper to analyze insider trading surrounding class action settlement announcements, and raises concerns about the ethical conduct of certain insider groups while highlighting the importance of access to private information, even amongst insiders themselves.